Communicative Leadership among Local Leaders in Indonesia during covid-19 Crisis Management - Laturrakhmi, Yun Fitrahyati; Oktaviani, Fitri Hariana; Kriyantono, Rachmat (Jurnal Komunikasi, 2023)
The covid-19 pandemic is one of the health crises that demand effective communication and timely, accurate, and culturally sensitive communication to reach coordinated and more effective responses. Regarding this function, communicative leadership becomes critical in reaching the success of a health crisis, particularly among local communities which are frequently associated with resistance towards health initiatives. This research is intended to explore the communicative leadership performed by local leaders in managing covid-19 pandemic from 2020 to 2022. To meet this aim, the present study employed interviews with 6 local leaders in Kabupaten Pasuruan, Jawa Timur as informants. This research revealed that in responding health crisis due to covid-19 pandemic, leadership involved communication to construct and negotiate meaning through shared narratives about covid-19. This leadership had been performed to help communities in the sense-making process about the pandemic through a series of strategies comprising (1) operating religious frame and local values to construct a shared reality about covid-19 pandemic and how to respond to it, (2) providing narratives as the evidence, (3) performing openness, presence and empathy. This research also found that maintaining sustainable coordination with the authorities is performed by local leaders to assure communities about the pandemic response plan, thus, community involvement in covid-19 measures could be developed easily. This study confirmed some previous research highlighting the importance of faith-based organizations (FBOs) in communication intervention in the health context and research on the importance of narrative to persuade people to adopt new health behaviours.